Localised sub-descemet haemosiderin deposit after localised haemorrhagic Descemet detachment - Bayoumi, Nader; Abdelghany, Elhoseiny Ali (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
A 56-year-old male patient on maximal topical intraocular pressure-lowering medications for primary open-angle glaucoma underwent combined trabeculotomy-trabeculectomy with mitomycin C for an uncontrolled intraocular pressure of 30 mmHg in the left eye. A localised sub-Descemet bleeding occurred during the sweep of the trabeculotome into the anterior chamber. The localised haemorrhagic Descemet detachment did not obscure the visual axis, and the intraocular pressure was controlled at 12 mmHg. Continued follow-up after 1 year revealed the localised sub-Descemet haemorrhage resolving into localised haemosiderin deposit, the visual acuity revealed slight improvement, and the intraocular pressure remained controlled.